Peran Otoritas Jasa Keuangan Dalam Melindungi Pemegang Polis Asuransi Akibat Pailitnya Perusahaan Asuransi - Imroatul Hasanah; Novilia Wulansari; Nur Aini Riski Yolandari; Firly Ajurni (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
The Financial Services Authority as an institution that controls insurance sector activities functions to create a financial system that grows sustainably and stably and increases public trust in the insurance sector. As part of supervision of the insurance sector, the Financial Services Authority has the authority to issue bankruptcy statements to insurance companies to protect the interests of policyholders. The aim of this research is to examine the role and jurisdictional perspective of the Financial Services Authority in insurance company bankruptcy cases in Indonesia. OJK is an independent institution that is free from state interference in carrying out its duties, roles and authority in the field of supervision, investigation and research in the financial services sector to create a good national economy. In supervising the insurance sector, the Financial Services Authority has the authority to file bankruptcy applications against insurance companies to protect the interests of policy holders. Insurance companies are regulated in Law no. 21 of 2011 concerning the Financial Services Authority. This research uses a qualitative descriptive approach, which is based on secondary data obtained through library research. The task of the Financial Services Authority in the bankruptcy of an insurance company is to monitor the progress of the insurance company's bankruptcy until its liquidation and to guarantee that the insurance company has paid all its obligations.